Considering the interdependence of clinical performance: implications for assessment and entrustment. Issue 9 (19th April 2018) - Sebok‐Syer, Stefanie S; Chahine, Saad; Watling, Christopher J; Goldszmidt, Mark; Cristancho, Sayra; Lingard, Lorelei
Abstract : Introduction: Our ability to assess independent trainee performance is a key element of competency‐based medical education (CBME). In workplace‐based clinical settings, however, the performance of a trainee can be deeply entangled with others on the team. This presents a fundamental challenge, given the need to assess and entrust trainees based on the evolution of their independent clinical performance. The purpose of this study, therefore, was to understand what faculty members and senior postgraduate trainees believe constitutes independent performance in a variety of clinical specialty contexts. Methods: Following constructivist grounded theory, and using both purposive and theoretical sampling, we conducted individual interviews with 11 clinical teaching faculty members and 10 senior trainees (postgraduate year 4/5) across 12 postgraduate specialties. Constant comparative inductive analysis was conducted. Return of findings was also carried out using one‐to‐one sessions with key informants and public presentations. Results: Although some independent performances were described, participants spoke mostly about the exceptions to and disclaimers about these, elaborating their sense of the interdependence of trainee performances. Our analysis of these interdependence patterns identified multiple configurations of coupling, with the dominant being coupling of trainee and supervisor performance. We consider how the concept of coupling could advance workplace‐based assessment efforts by supporting models that account for the collective dimensions of clinical performance. Conclusion: These findings call into question the assumption of independent performance, and offer an important step toward measuring coupled performance. An understanding of coupling can help both to better distinguish independent and interdependent performances, and to consider revising workplace‐based assessment approaches for CBME. Abstract : The authors put forth coupling as a bridge between the traditional assessment focus on independent performance and the emerging assessment challenge of accounting for collective performance.